Critical Peripheral Fatigue Thresholds Among Different Force-Velocity Conditions: An Individual-Based Model Approach - Morel, Baptiste; Lapole, Thomas; Liotard, Cyril; Hautier, Christophe (Frontiers in Physiology, 2019)
During high intensity exercise, metabosensitive muscle afferents are thought to inhibit the motor drive command to restrict the level of peripheral fatigue to an individual’s critical threshold. No evidence exists of an individual relationship between peripheral fatigue and the decrease in voluntary activation reached after prolonged all-out exercise. Moreover, there is no explanation for the previously reported large decrease in voluntary activation despite low metabolic stress during high force contractions. Thirteen active men completed two maximal intensity isokinetic knee extension tests (160 contractions) under conditions of low force - high velocity and high force – low velocity. Neuromuscular testing including maximal torque, evoked torque and voluntary activation, was done every 20 contractions. The exponential modeling of these variables over time allowed us to predict the stable state (asymptote) and the rate of decrease (curvature constant). For both high and low force contractions the evoked torque and voluntary activation asymptotes were negatively correlated (R²=0.49 and R² = 0.46, respectively). The evoked torque asymptotes of the high and low force conditions were positively correlated (R²=0.49). For the high force contractions, the evoked torque and voluntary activation curvature constant were negatively correlated (R²=0.43). These results support the idea that a restrained central motor drive keeps peripheral fatigue under this threshold. Furthermore, an individual would show similar fatigue sensibility regardless of the force generated. These data also suggest that the decrease in voluntary activation might not have been triggered by peripheral perturbations during the first high force contractions.